Bilateral posterior fossa and temporo-occipital extra-dural hematomas: A simple novel technique - Aggarwal, Ashish; Salunke, Pravin; Futane, Sameer; Sodhi, Harsimrat (Asian Journal of Neurosurgery, 2017)
Posterior fossa extra-dural hematoma is rare and early diagnosis and management is associated with good outcome. Twenty four year male presented with somnolence and soft tissue swelling of occipital region following road traffic accident. CT scan revealed bilateral posterior fossa with bilateral temporo-occipital Extradural Hematoma (EDH) with mass effect. He was operated through a trifoliate incision and craniotomies leaving a strip of bone over the transverse and occipital sinus. The blood loss with such technique was minimal and the control of sinus tear was easier as the dura on either sides of the sinus can to tied to each other to hitch the sinus up to the bone thereby, providing a good tamponade. Early diagnosis of posterior fossa EDH and prompt surgical evacuation especially in patients with mass effect provide excellent recovery. However, the surgery may be associated with significant blood loss due to venous sinus injury increasing the morbidity and mortality. We have described a novel technique that minimizes the blood loss for patients with PFEDH straddling across the venous sinuses.
Keywords: Bilateral; extradural hematomas; posterior fossa